Students’ Perception of Teachers’ Pedagogical and Personal Competences and Their Learning Outcomes: A Correlational Study at SMPN 1 Bandar Seikijang - Bagus Tri Saputra; Suriyah Suriyah; Siti Fatimah Siregar (Kutubkhanah, 2023)
The objective of this research was to know about the effectiveness of teacher’s pedagogical and personal competence toward students’ motivation and learning outcomes in SMPN 1 Bandar Seikijang. The researcher applied quantitative methods with a multiple regressions design. The samples of this research was the 85 students. The technique of collecting data by using questionnaire. Based on the result of this research, Pedagogical Competence has a significant effect on Learning Outcomes. Therefore, the H1 hypothesis is accepted by the decision rule, namely the more teachers’ pedagogical competence is good, then learning outcomes will be higher. Personal Competence has a significant effect on Learning Outcomes. Therefore, the H2 hypothesis is accepted by the decision rule, namely the more teachers’ personal competence is good, then learning outcomes will be higher. Students’ Motivation has a significant effect on Learning Outcomes. The variables of pedagogical competence and personal competence together have a significant effect on learning outcomes. Therefore, H3 is accepted with the decision rule.